Engineering design : a project based introduction - Dym, Clive L.; Little, Patrick ([S.l.] : Wiley, 2008)
Engineers continue to turn to Engineering Design to learn the tools and techniques of formal design that will be useful in framing the design problems. Insights and tips on team dynamics are provided because design and research is increasingly done in teams. Readers are also introduced to conceptual design tools like objectives trees, morphological charts, and requirement matrices. Case studies are included that show the relevance of these tools to practical settings. The third edition offers a view of the design tools that even the greenest of engineers will have in their toolbox in the coming years.